The carbocyclic analog of 2'-deoxyguanosine induces a prolonged inhibition of duck hepatitis B virus DNA synthesis in primary hepatocyte cultures and in the liver. - Fourel, I (1994)
The carbocyclic analog of 2'-deoxyguanosine (2'-CDG) is a strong inhibitor of hepatitis B virus (HBV) DNA synthesis in HepG2 cells (P.M. Price, R. Banerjee, and G. Acs, Proc. Natl. Acad. USA 86:8543-8544, 1989). We now report that 2'-CDG inhibited duck hepatitis B virus (DHBV) DNA synthesis in primary cultures of duck hepatocytes and in experimentally infected ducks. Like foscarnet (phosphonoformic acid [PFA]) and 2'-,3'-dideoxycytidine (ddC), 2'-CDG blocked viral DNA replication in primary hepatocyte cultures when present during an infection but failed to inhibit the DNA repair reaction that occurs during the initiation of infection to convert virion relaxed circular DNA to covalently closed circular DNA, the template for viral mRNA transcription. Moreover, as for PFA and ddC, viral RNA synthesis was detected when infection was initiated in the presence 2'-CDG. In another respect, however, 2'-CDG exhibited antiviral activity unlike that of ddC or PFA: a single 1-day treatment of hepatocytes with 2'-CDG blocked initiation of viral DNA synthesis for at least 8 days, irrespective of whether DHBV infection was carried out at the time of drug treatment or several days later. Furthermore, orally administered 2'-CDG was long-acting against DHBV in experimentally infected ducklings. Virus replication was delayed by up to 4 days in ducklings infected after administration of 2'-CDG. These observations of long-lasting efficacy in vitro and in vivo even after oral administration suggest that this inhibitor or a nucleoside with similar pharmacological properties may be ideal for reducing virus replication in patients with chronic HBV infection.